Bitter substances from plants used in traditional Chinese medicine exert biased activation of human bitter taste receptors. (14th September 2017) - Behrens, Maik; Gu, Ming; Fan, Shengjie; Huang, Cheng; Meyerhof, Wolfgang
Abstract : The number and variety of bitter compounds originating from plants are vast. Whereas some bitter chemicals are toxic and should not be ingested, other compounds exhibit health beneficial effects, which is manifest in the cross‐cultural believe that the bitterness of medicine is correlated with the desired medicinal activity. The bitter taste receptors in the oral cavity serve as sensors for bitter compounds and, as they are expressed in numerous extraoral tissues throughout the body, may also be responsible for some physiological effects exerted by bitter compounds. Chinese herbal medicine uses bitter herbs since ancient times for the treatment of various diseases; however, the routes by which these herbs modify physiology are frequently not well understood. We therefore screened 26 bitter substances extracted from medical herbs for the activation of the 25 human bitter taste receptors. We identified six receptors activated by in total 17 different bitter compounds. Interestingly, we observed a bias in bitter taste receptor activation with 10 newly identified agonists for the broadly tuned receptor TAS2R46, seven agonists activating the TAS2R14 and two compounds activating narrowly tuned receptors, suggesting that these receptors play dominant roles in the evaluation and perhaps physiological activities of Chinese herbal medicines. Abstract : To identify the human bitter taste receptors activated by bitter substances present in plants used in Chinese herbal medicine, compounds were extracted from these plants and purified. In total 26 bitter compounds were subjected to a functional screening of all 25 human bitter taste receptors. We identified 17 substances activating 6 receptors, which may be particularly important for the taste and potentially some of the physiological activities of medicinal herbs.